Arvets betydelse för mjölkkors beteende - Bengtsson, Caroline (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2008)
It becomes more important to consider different behaviour traits in the selection for dairy cows to be suitable in the production systems of today. The purpose of this investigation was to study the genetic background to behavioural traits and the heritabilities for temperament, rank order, aggressiveness, feeding behaviour and for learning behaviour. Moreover, the genetic correlations to other traits were studied. To be included in a breeding programme a trait needs to have enough genetic variation, a moderate to high heritability or to be correlated to another measurable trait. Behaviour is a quantitative trait affected by many genes and the environment. The temperament of dairy cows has a moderate to high heritability and is also highly genetic correlated to milkability, milk yield, growth and carcass traits. The feeding behaviour does not differ much between different individuals or breeds. The rank order is positively correlated to body size within breed, but not between breeds, while aggressiveness and learning behaviour is mostly influenced by the environment. A part of the genome in cattle is mapped with associations to behaviour traits.